2017
DOI: 10.1159/000477781
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Impact of Early Nutrition: The Power of Programming

Abstract: The Power of Programming conference 2016 at Ludwig-Maximilians-Universität Munich brought together about 600 researchers and other stakeholders from around the world who reviewed the recent evidence on the lasting health impact of environment and nutrition during early life, from pre-pregnancy to early childhood. The conference was hosted by the Early Nutrition Project, a multidisciplinary research collaboration funded by the European Commission with collaborating researchers from 35 institutions in 15 countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 34 publications
(42 reference statements)
1
85
0
7
Order By: Relevance
“…Although the order between weight faltering and catch-up gain was opposite, a cohort study in South Africa reported that a transient catch-up weight gain during infancy, followed by weight growth faltering, is linked to higher adiposity in early adulthood [24]. Taken these studies, systematic reviews, meta-analysis, and proposals together, 1 hypothesis might be that the association found in the 7 cases presented here between AWG and overweight status at 3 years of age is influenced by a mismatch in postnatal under-nutrition and subsequent over-nutrition until early childhood, similar to the mismatch seen between fetal programming as an epigenetic change and subsequent postnatal catch up growth [20]. However, the possibility that the regulation and programming of growth rates during postnatal early life is altered only by a short period of PSWG remains to be established.…”
Section: Exposuresupporting
confidence: 54%
See 1 more Smart Citation
“…Although the order between weight faltering and catch-up gain was opposite, a cohort study in South Africa reported that a transient catch-up weight gain during infancy, followed by weight growth faltering, is linked to higher adiposity in early adulthood [24]. Taken these studies, systematic reviews, meta-analysis, and proposals together, 1 hypothesis might be that the association found in the 7 cases presented here between AWG and overweight status at 3 years of age is influenced by a mismatch in postnatal under-nutrition and subsequent over-nutrition until early childhood, similar to the mismatch seen between fetal programming as an epigenetic change and subsequent postnatal catch up growth [20]. However, the possibility that the regulation and programming of growth rates during postnatal early life is altered only by a short period of PSWG remains to be established.…”
Section: Exposuresupporting
confidence: 54%
“…): fetal over-nutrition, accelerated postnatal growth, and a mismatch between fetal under-nutrition and postnatal over-nutrition [19,20]. Interestingly, a large longitudinal prospective cohort study has reported that term infants exhibiting early slow weight gain (<-1.645SDS) during the first 8 weeks of life returned to a normal mean weight SDS through recovery up to 2 years of age, and also remained around a normal weight range until 13 years of age [2].…”
Section: Discussionmentioning
confidence: 99%
“…During this period, phenotypic development is more susceptible to change in response to environmental factors, although there is also evidence that (a) nutritional status before conception is also important, and (b) there is ongoing plasticity (albeit more limited) beyond this period [19,20]. Early nutrition is arguably one of the most significant environmental determinants of an offspring's cell structure, epigenome, metabolome, hormones and microbiome [16,19]. Epigenetic modification of gene expression could be one of the key pathways through which early nutrition may modify the developing phenotype, thereby inducing powerful effects on long-term health trajectories and disease risk [2,20].…”
Section: Early Nutrition Programming: the Conceptmentioning
confidence: 99%
“…The most studied epigenetic modifications include histone modification, non-coding RNAs and DNA methylation [20]. Nutritional effects on the latter have been documented and represent a logical mechanism to explain the relationship between early nutrition and long-term health [2,14,16,22]. While the concept of early nutrition programming and the long-term repercussions has been widely accepted by the scientific community [16,23], this concept is still largely unknown to many women and healthcare providers.…”
Section: Early Nutrition Programming: the Conceptmentioning
confidence: 99%
See 1 more Smart Citation